An exploratory qualitative study of the prevention of road traffic collisions and neurotrauma in India: perspectives from key informants in an Indian industrial city (Visakhapatnam) - Santhani M Selveindran; Gurusinghe D. N. Samarutilake; K. Madhu Narayana Rao; Jogi V. Pattisapu; Christine Hill; Angelos G. Kolias; Rajesh Pathi; Peter J. A. Hutchinson; M. V. Vijaya Sekhar (BMC, 2021)
Abstract Background Despite current preventative strategies, road traffic collisions (RTCs) and resultant neurotrauma remain a major problem in India. This study seeks to explore local perspectives in the context within which RTCs take place and identify potential suggestions for improving the current status. Methods Ten semi-structured interviews were carried out with purposively selected key informants from the city of Visakhapatnam, Andhra Pradesh. Participants were from one of the following categories: commissioning stakeholders; service providers; community or local patient group/advocacy group representatives. Transcripts from these interviews were analysed qualitatively using the Framework Method. Results Participants felt RTCs are a serious problem in India and a leading cause of neurotrauma. Major risk factors identified related to user behaviour such as speeding and not using personal safety equipment, and the user state, namely drink driving and underage driving. Other reported risk factors included poor infrastructure, moving obstacles on the road such as other vehicles, pedestrians and animals, overloaded vehicles and substandard safety equipment. Participants discussed how RTCs affect not only the health of the casualty, but are also a burden to the healthcare system, families, and the national economy. Although there are ongoing preventative strategies being carried out by both the government and the community, challenges to successful prevention emerged from the interviews which included resource deficiencies, inconsistent implementation, lack of appropriate action, poor governance, lack of knowledge and the mindset of the community and entities involved in prevention. Recommendations were given on how prevention of RTCs and neurotrauma might be improved, addressing the areas of education and awareness, research, the pre-hospital and trauma systems, enforcement and legislation, and road engineering, in addition to building collaborations and changing mindsets. Conclusions RTCs remain a major problem in India and a significant cause of neurotrauma. Addressing the identified gaps and shortfalls in current approaches and reinforcing collective responsibility towards road safety would be the way forward in improving prevention and reducing the burden.